CH4 and H2S reforming to CH3SH and H2 catalyzed by metal-promoted Mo6S8 clusters: a first-principles micro-kinetic study. Issue 16 (26th July 2017) - Taifan, William; Arvidsson, Adam A.; Nelson, Eric; Hellman, Anders; Baltrusaitis, Jonas
Abstract : Density Functional Theory (DFT) and microkinetic modelling of CH4 and H2 S reactions to form CH3 SH and H2 as a first step in elucidating complex pathways in oxygen-free sour gas reforming was performed. Abstract : Direct processing of sour, e.g. containing large amounts of acidic H2 S and/or CO2 molecules, natural gas is of direct interest as vast amounts of it are available and accessible but are underutilized. While sour natural gas is still treated using energy-intensive amine absorption/desorption, here we propose and describe a first step in catalytically producing a value added chemical and energy carrier, CH3 SH and H2, respectively. For this purpose, we performed Density Functional Theory (DFT) and microkinetic modelling of CH4 and H2 S reaction pathways to form CH3 SH and H2 as a first step in elucidating complex yet not explored pathways in oxygen-free sour gas reforming. For this purpose, we utilized bare unpromoted and K- or Ni-promoted Mo6 S8 clusters. CH4 dissociation was found to be the rate-determining step above 1100 K on Ni-promoted Mo6 S8 while H2 formation was the rate-determining step on the bare and K-promoted Mo6 S8 . At lower reaction temperatures between 800 and 1100 K, CH3 SH formation becomes an important step, especially on Ni–Mo6 S8 . This method presents an interesting route of direct catalytic sour natural gas processing which potentially leads to high-value hydrocarbons, such as ethylene, using CH3 SH as a reactive intermediate.